METHODOLOGY OF TRAINING PRACTICE BODIES IN THE DIRECTION OF PREVENTING AND RESOLVING EMERGENCY SITUATIONS AND ENSURING FIRE SAFETY IN THE LIFE SAFETY COURSE (Scientific journal of the Fergana State University, 2024)
In this article, the scientific proposal and recommendations about the essence, principles and specific aspects of the use of modern pedagogical technologies in teaching the life safety course to the practice bodies of the Republic of Uzbekistan are covered